Diagnosis of isolated intracardiac cement embolism causing cardiac rupture via bedside transthoracic echocardiography: a case report - Chen, Fei; Li, Cong; Chen, Yu-Jia; Hu, Yan-Ze (BMC cardiovascular disorders, 2025)
Bone cement leakage is a common complication of percutaneous vertebroplasty and may lead to severe complications such as intracardiac cement embolism. Bedside transthoracic echocardiography serves as a crucial tool in the diagnosis of intracardiac cement embolism. An elderly female developed acute sharp chest pain with ST-segment depression two hours postvertebroplasty and was initially suspected to have acute myocardial infarction according to her symptoms/ECGs. Bedside transthoracic echocardiography excluded the diagnosis of wall motion abnormalities but revealed a linear, highly echogenic structure within the right atrium and ventricle chambers. One end of the structure pierced the anterior wall of the right ventricle, and a small volume of pericardial effusion was detected. By integrating the patient's history of bone cement injection, sonographers quickly changed the diagnosis from infarction to cardiac rupture by cement embolism. A chest computed tomography (CT) scan revealed no abnormalities in the pulmonary artery or its distal branches. The clinicians were able to diagnose isolated intracardiac cement embolism in a timely manner. Surgical thoracotomy was performed to remove the cement from the heart and repair the right ventricle rupture. The patient's postoperative recovery went smoothly. Bedside transthoracic echocardiography may aid in the timely diagnosis of intracardiac cement embolism and characterization of its features and assist in the assessment of associated severe complications. This case report can serve as a valuable reference for guiding clinical diagnosis and treatment decisions.